Penerapan Alat-Alat Pendidikan Islam Pada Mata Pelajaran Sejarah Kebudayaan Islam - Rijal, Akhyarur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The subject of Islamic Cultural History is one of the subjects that has an important role in learning Islamic values to students. Realizing the important role that must always be instilled in the teachers of Islamic Cultural History, the researcher aims to examine the essence of the application of Islamic educational tools in optimizing the Islamic Cultural History learning process. This research is a descriptive study with a qualitative approach. The results of the study indicate that these teachers are quite aware of the importance of the effective implementation of the Islamic Cultural History knowledge transfer process. Islamic educational tools, there are at least 5 types that according to the teachers' confessions are quite often used, although only a few. The 5 tools are; physical, method, environment, values and teacher role models, and modern technology. There are six functions of Islamic educational tools that have been applied by teachers of Islamic Cultural History, namely; clarifying learning materials, increasing learning motivation, helping to form habits and skills, facilitating a pleasant learning experience, increasing communication effectiveness and helping to evaluate learning. In addition, there are 5 other functions in the process of applying these Islamic educational tools to learning, namely; improve learning effectiveness, support creativity, improve student concentration, create a conducive learning environment and connect theory and practice.